(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. La valenza costituzionale della riforma della Curia romana - 2. La linea della ‘universalitas participata et pluralis Ecclesiae’ - 3. I beni della comunione e l’architettura delle Istituzioni curiali - 4. La congenita strumentalità dell’Istituzione curiale - 5. L’orizzonte istituzionale del servizio della Curia romana - 5.1. La vicarietà potestativa - 5.2. La cooperazione organica al servizio primaziale - 5.3. La corresponsabilità decentralizzante - 6. L’orizzonte personale del servizio della Curia romana - 6.1. La professionalità e la laicità - 6.2. La pastoralità e la spiritualità - 6.3. L’universalità e la temporaneità degli incarichi - 7. La promozione della razionalità e funzionalità della Curia - 8. Il cammino sinodale della riforma. A ‘Structural’ Reading of “Praedicate Evangelium” ABSTRACT: The article examines the (indirect and limited) constitutional value of the reform of the Roman Curia. The basic framework of Praedicate Evangelium is connected to the missionary impulse instilled by pontificate of Francis in the shared and plural structure of universality. The service of the Curia to the Church and to the world is founded upon its instrumental institutional character and on the maximum possible distribution of and participation in the goods of communion. Beyond the regulative aspects, this normative intervention develops various vectors and features of organization. At the institutional level, the vicarious dimension of power, the organic cooperation between the curial institutions and the decentralizing co-responsibility in the role of the episcopacy emerge. At the personal level, there is the encouragement of professional roles, of laity, of pastorality and spirituality, of the universality, and of the temporary nature of the offices. The criteria of rationality and functionality synthesize the aspiration to revise the central government. The reform of the Curia denotes a significant passage of the synodal way of the Church, which provides reasons for certain ecclesiological and speculative analysis, as well as for the perfection of canonical knowledge from a constitutional viewpoint.